Perawatan resesi gingiva dengan bedah dan non-bedah - Noer Ulfah; Eka Fitria Augustina (DiscoverSys Inc., 2010)
Gingival recession is an exposed root surfaces that caused by shifting gingiva towardapical, and often causes problem. Gingival recession can occur locally or generally atall teeth causing dentin hypersensitive and susceptible to caries. Other problem is thelack of aesthetic, especially on anterior teeth. Treatment of all kinds of gingivalrecession depends on the severity and causes of recession. Treatments addressed toovercome the aesthetic problem and hypersensitivity of dentin. Mucogingival surgeryis preferred to position the flap coronally. Non surgical techniques have beendeveloped to solve the problem of aesthetic and hypersensitive dentin. The method isconducted to using of artificial gingiva on the recession area. Regular control isneeded to maintain good oral hygiene in order to protect or to avoid the recession.